Clinical-pathological characteristics and risk factors for oral squamous cell carcinoma in young patients - Leonardo Magalhães Carlan; Maria de Lourdes Silva de Arruda Morais (RGO: Revista Gaúcha de Odontologia)
ABSTRACT Objective To evaluate the clinical-pathological characteristics and risk factors of patients with young oral squamous cell carcinoma at a referral service in oncology. Methods A retrospective analysis of 12 patients diagnosed with squamous cell carcinoma in the oral cavity treated between 2006 and 2015 was performed, and the following data were collected: age, sex, habits, anatomical location of the lesion, clinical stage of the tumor, time of disease, clinical characteristics, histological gradation, comorbidities, family history of cancer, therapeutic modality and outcome. Results The average age found was 39 years old (SD ± 5.3). Most of the sample consisted of male individuals (n=9; 75%), risk factors were present in 5 patients (41.6%) and the most affected site was the tongue (n=7; 58, 3%). Symptoms were present in most patients (n=7; 58.3%) studied, as well as clinical staging III and IV (n=9; 75%). Surgery associated with radio and/or chemotherapy was used in 5 cases (41.7%) and most patients died. Conclusion Most of the patients had advanced clinical stage, leading to high rates of recurrence and therapeutic failure, contributing to a negative prognosis and high mortality rates.